Enterprise Resource Planning Accelerates Sales Administration And Feed Distribution: Perencanaan Sumber Daya Perusahaan Mempercepat Administrasi Penjualan Dan Distribusi Pakan - Rafli Bahtiar; Ika Oktaviyanti (International Consortium of Education and Culture Research Studies, 2024)
General Background The agricultural industry increasingly relies on integrated technological systems to ensure operational speed and accurate product deliveries. Specific Background PT Japfa Comfeed Indonesia utilizes Systems Applications and Products in Data Processing to manage real-time inventory, prioritize orders, and design delivery routes for livestock nourishment. Knowledge Gap Although integrated software consolidates business functions, the difficulties employees face when transitioning from manual methods to complex digital interfaces remain underexplored. Aims This study investigates the utilization of enterprise software by administrative staff to identify strategies for optimizing operational procedures and expedition handling. Results Qualitative analysis employing observation and a fishbone diagram reveals that software adoption reduces order completion time by fifteen percent and decreases data input mistakes by twenty percent. Conversely, employees experience difficulties adapting to unintuitive system interfaces, leading to human errors and workflow delays. Novelty This research maps specific socio-technical bottlenecks, categorizing human, method, material, and environmental challenges within agribusiness logistics software transitions. Implications Organizations must provide continuous technical training and simplify system navigation to secure employee adaptation, thereby maximizing logistics agility and customer satisfaction. Highlights: Digital integration reduces order completion time and minimizes manual input mistakes. Unintuitive software interfaces trigger employee resistance during technological transitions. Continuous technical training secures operational agility and logistics accuracy. Keywords: Agribusiness Operations, Expedition Handling, Order Processing, Technology Adaptation, Logistics Management